African Religion, Climate Change, and Knowledge Systems - Tarusarira, Joram (The Ecumenical Review, 2017)
This article argues that as humanity is now changing the composition of the atmosphere at a rate that is very exceptional on the geological time scale, resulting in global warming, humans must deal with climate change holistically, including the often overlooked religion factor. Human-caused climate change has resulted primarily from changes in the amounts of greenhouse gases in the atmosphere, but also from changes in small particles (aerosols), as well as from changes in land use. In Africa, the entire relationship between humans and nature, including activities such as land use, has deep religious and spiritual underpinnings. In general, religion is central to many of the decisions people make about their own communities’ development. Hence, this contribution examines religion as a factor that can be tapped into to mitigate negative effects of climate change, discussing climate change and religion in the context of development practice. It argues that some of the difficulties encountered in development, including efforts to reverse global warming in Africa, directly speak to the relegation of African cosmovision and conversely of the need to adopt new epistemologies, concepts, and models that take religion into consideration.
free
Keywords: Christianity and African religions; Climate change mitigation; Ethnoscience; Global warming